Recognition of behavioral problems in preschool children from the educator's point of view - Milenović, Hadži Živorad; Jeremić, Biljana; Markov, Zagorka (Specijalna edukacija i rehabilitacija, 2024)
Introduction. The research problem is formulated in the form of research questions: can educators recognize problems in the behavior of preschool children, and are they sufficiently competent to undertake planning actions related to the prevention and suppression of externalized and internalized problems in the behavior of preschool children? Objectives. The goal of the research was to determine whether educators can recognize problems in the behavior of preschool children and take measures to overcome these problems. Methodes. The research was conducted in January 2023 on a sample of 124 educators from the areas of Bačka and Banat. The teacher’s assessment of the recognition of problems in the behavior of preschool children was examined with the Scaler - RBDCPA-EP constructed for the purposes of this research (α = .822). It consists of three subtests: 1) recognition of behavioral problems in preschool children; 2) informing parents and professional associates about observed problems in the behavior of preschool-age children; and 3) taking action to narrow down behavioral problems. Results. The results of the research show that problems in the behavior of preschoolage children can be predictive factors that show behavioral disorders in adolescence. Conclusion. It is concluded that, besides the primary role of educators, it is necessary to undertake a series of planned actions so that preschool institutions provide optimal support for children with behavioral problems and their families.
Keywords: behavior; early identification; inclusion in education; developmental disabilities; obstacles in education; internalizing problems; externalized problems